Pencegahan Kejahatan Siber Terkait Distribusi Perjudian Online di Indonesia dalam Rangka Mewujudkan Keamanan dan Ketertiban Masyarakat - Daniel Hasianto Hendarto; Riska Sri Handayani (Syntax Corporation Indonesia, 2024)
This research aims to explore policing strategies in the prevention of online gambling crimes. The focus of this paper is to identify the characteristics and development of online gambling crimes, the factors that contribute to the implementation of the crime prevention strategy at the Directorate of Cyber Crime of the Criminal Investigation Unit of the National Police, and the ideal policing strategy in preventing such crimes. The theoretical perspectives used in this research are Sittuational Crime Prevention theory and Partnership Theory. The results of this study explain that in efforts to prevent online gambling crimes, development is needed related to various strategies and approaches in preventing these crimes, this is because the development of online gambling that has occurred today cannot be matched by crime prevention efforts carried out by the Police and related Government Institutions.